Congenital gingival cyst of neonate: Dentist's enigma - Deepak Chauhan; Kapil Rajiv Sharma; Jai Ram Kaundal; Seema Thakur; Kshitiz Parasher; Tripti Chauhan (Wolters Kluwer Medknow Publications, 2013)
Gingival cysts of the newborn are small keratin-filled cysts on the alveolar mucosa of infants that exists at birth. They are remnants of the dental lamina and are usually multiple in numbers, but do not increase in size. The diagnosis is made at the clinical level. Since, this lesion tends to undergo involution or regresses spontaneously within a few weeks or months after birth so unnecessary therapeutic intervention is avoided. Complications are rarely observed. Pain on sucking, refusal to feed and airway obstruction can occur in rare instances. However parents remain anxious about the prevailing condition. Hence they should be reassured by providing suitable information about the simple nature of this lesion.